Counting people nineteenth-century population history of four Manila Arrabales using the Planes de Almas - Gealogo, Francis A. (Quezon City Ateneo de Manila University, 2011)
"Along with the profound social and political transformation, the arrabales (suburbs) of Intramuros, Manila, also underwent significant demographic changes during the nineteenth century as indicated by population growth, urbanization, rising population density, and changes in death, birth, and marriage rates. This paper utilizes quantitative data from the Planes de Almas, the numerical summaries of population data of different parishes found in the Archdiocesan Archives of Manila, to analyze the population history of these suburbs. These data concern burials, baptisms, and marraiges, as well as reports on taxation and the confessional status of inhabitants.
Research note.
Keywords: Population -- Metro Manila; Urban population history; Demographic history; Spanish colonialism